Manajemen Tabungan Ibu Bersalin (TABULIN) Mandiri Menggunakan Dompet Mandiri Keuangan Solusi Menurunkan Kecemasan Finansial - Aida Ratna Wijayanti; Choirul Hamidah; Inna Sholicha Fitriani (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
One of the efforts to reduce the Maternal Mortality Rate and Infant Mortality Rate are thought to reduce the anxiety level of pregnant women and mothers giving birth, one way to reduce the level of anxiety is to prepare funds for childbirth early. The method used is to provide direct education in pregnant women’s classes about maternity savings, and provide assistance by online to filling financial smart wallets. The number of participants who took part in the antenatal class was 28 pregnant women, spread over of the Ronowijayan Public Health Center. Output target is the achievement of saving one million rupiah within three months, the results obtained have not yet reached that target. The evaluation was carried out through indirect communication and part of the reason why the service outcome had not been achieved were that some pregnant women had their own methods of saving, some in the form of crops, gold, or livestock that could be sould if needed at any time. Although it is still not effective, there are efforts to set aside some money to be saved in financial independent wallet.